2009
DOI: 10.1111/j.1365-2567.2009.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine regulates CD8 T‐cell priming by inhibition of membrane‐proximal T‐cell receptor signalling

Abstract: Summary Adenosine is a well‐described anti‐inflammatory modulator of immune responses within peripheral tissues. Extracellular adenosine accumulates in inflamed and damaged tissues and inhibits the effector functions of various immune cell populations, including CD8 T cells. However, it remains unclear whether extracellular adenosine also regulates the initial activation of naïve CD8 T cells by professional and semi‐professional antigen‐presenting cells, which determines their differentiation into effector or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 57 publications
(117 reference statements)
9
84
0
Order By: Relevance
“…It is also known that adenosine prevents the priming of naïve CD8 cytotoxic T cells [26] by antigen-presenting cells. In our study, IgG deposition in the glomeruli was associated with the presence of CD25+activated CD8+T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that adenosine prevents the priming of naïve CD8 cytotoxic T cells [26] by antigen-presenting cells. In our study, IgG deposition in the glomeruli was associated with the presence of CD25+activated CD8+T cells.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Adenosine, which is present at increased concentrations in cancer tissue, 29,30 has a crucial role in the activity alteration of immune cells including Tregs 31 and CD8 C T cells. 32 We found that a large fraction of CD39 C gdT cells co-expressed CD73 (Fig. 4A).…”
Section: Tumor-infiltrating Cd39 C Gdt Cells Have Potent Immunosupprementioning
confidence: 95%
“…47,48 Additionally, stimulation of A 2A adenosine receptors suppresses the production of interferon-γ (IFN-γ) and IL-4 by both naive CD4 + T cells and polarized type 1 T helper (T H ) cells and T H 2 cells. 11,47,49,50 Similarly, adenosine suppresses the activity of naive CD8 + T cells 51 and controls the effector functions of fully differentiated CD8 + T cells. 49,52,53 However, the role of adenosine in regulating T cell functions at onset of T1DM is incompletely understood.…”
Section: Immune Cellsmentioning
confidence: 98%